O peso dos determinantes sociais da saúde na vida dos sujeitos bariátricos : desafios para o SUS - Scherer, Patricia Teresinha (2015)
Obesity is considered a world epidemic and it implies severe consequences to health besides psychosocial difficulties. As an alternative for the treatment of obesidty, the bariatric surgery is recommended in cases of morbid or moderate obesity with related diseases.The present thesis introduces a research made for Doctorate Degree in Social Service at the Catholic University of Rio Grande do Sul carried out at the Center of Obesity and Metabollic Syndrome of São Lucas Hospital which belongs to PUCRS (COM). It is a qualitative research with the general objective of investigating the way how health social determinants interfere in the bariatric post-surgery process of people submitted to this procedure in the scope of the Unified Health System (SUS). The data collection was done by means of a form with semi-structured script that comprised open and closed questions. A total of 27 subjects were interviewed in the period from September 2013 to November 2014 and the answers were submitted to the technique of Content Analysis.The dialectical and critical background guided the construction of the research and the sistematization of the obtained results.The investigative proposal was submitted to the Scientific Commission of the School of Social Service of PUCRS and to the Ethics Committee in Research of the same University. Findings indicate that health social determinants may compromise the surgery results and the subjects undergoing vulnerability shall have difficulties of access and maintenance of the post-operative treatment as recommended by the bariatric team. Among the factors that make it difficult to meet the post-operative recommendations are: difficulties to attend the follow-up appointments, financial difficulties, lack of preparation of the healthcare network to serve the bariatric users, besides the need of specific and broad public policies for the bariatric process. Users point out positive changes and benefits like the post-operative slimming, especially regarding health and social relations, what evidences the importance of the public investment in the bariatric surgery.